Uncover the anticancer potential of lycorine - Yan-Ming Zhang; Ting Li; Chun-Cao Xu; Jia-Yu Qian; Hongwei Guo; Xiaolei Zhang; Zha-Jun Zhan; Jin-Jian Lu (BMC, 2024)
Abstract Background Natural products have a long history in drug discovery. Lycorine is an alkaloid derived from Amaryllidaceae plants, demonstrating significant pharmacological potential. Lycorine and its hydrochloride salt, lycorine hydrochloride, have shown outstanding anticancer effects both in vitro and in vivo. Purpose This review aims to comprehensively summarize recent research advancements regarding the anticancer potential of lycorine and lycorine hydrochloride. It intends to elucidate current research limitations, optimization strategies, and future research directions to guide clinical translation. Methods Various databases, e.g., Web of Science, PubMed, and Chinese National Knowledge Infrastructure, are systematically searched for relevant articles using keywords such as lycorine, cancer, pharmacokinetics, and toxicity. The retrieved literature is then categorized and summarized to provide an overview of the research advancements in the anticancer potential of lycorine and lycorine hydrochloride. Results Lycorine and lycorine hydrochloride demonstrate significant anticancer activities against various types of cancer both in vitro and in vivo, employing diverse mechanisms such as inducing cell cycle arrest, triggering cellular senescence, regulating programmed cell death, inhibiting angiogenesis, suppressing metastasis, and modulating immune system. Furthermore, pharmacokinetic profiles and toxicity data are summarized. Additionally, this review discusses the druggability, limitations, optimization strategies, and target identification of lycorine, offering insights for future preclinical studies. Conclusion The anticancer effects and safety profile of lycorine and lycorine hydrochloride suggest promising potential for clinical applications. Further research on their in-depth mechanisms and optimization strategies targeting their limitations will enhance the understanding and druggability of lycorine and lycorine hydrochloride. Graphical Abstract